2013
DOI: 10.1186/1471-2091-14-34
|View full text |Cite
|
Sign up to set email alerts
|

Development of an ELISA assay for the quantification of soluble huntingtin in human blood cells

Abstract: BackgroundHuntington’s disease (HD) is a monogenic disorder caused by an aberrant expansion of CAG repeats in the huntingtin gene (HTT). Pathogenesis is associated with expression of the mutant (mHTT) protein in the CNS, with its levels most likely related to disease progression and symptom severity. Since non-invasive methods to quantify HTT in the CNS do not exist, measuring amount of soluble HTT in peripheral cells represents an important step in development of disease-modifying interventions in HD.ResultsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
14
1
Order By: Relevance
“…Blood and CSF Htt protein levels remain fairly low, with a minimum requirement of a 50 ml blood sample to successfully detect Htt protein. In addition to variations in Htt protein concentrations with different blood cell types [165] , [166] , [167] . In a study conducted by Bloom et al.…”
Section: Huntington's Diseasementioning
confidence: 99%
“…Blood and CSF Htt protein levels remain fairly low, with a minimum requirement of a 50 ml blood sample to successfully detect Htt protein. In addition to variations in Htt protein concentrations with different blood cell types [165] , [166] , [167] . In a study conducted by Bloom et al.…”
Section: Huntington's Diseasementioning
confidence: 99%
“…The neuropsychiatric battery included the EHDN Problem Behaviours Assessmentshort version (PBA-s) [15], the Hospital Anxiety and Depression Scale [16] combined with the Snaith Irritability Scale (HADS-SIS) [17] and a modified version of the Frontal Systems Behavioural Scale, which was completed by the participants (FrSBe-p) [18]. This modified version of the FrSBe contains 24 items to assess the frequency of certain behaviours and the level of distress caused by those behaviours, but in contrast to the original version we did not use reverse coding for several questions (items [19][20][21][22][23][24], since the reverse coding was confusing for HD patients in a previous study [18]. The cognitive battery included trail making tests A and B [19], symbol digit modalities test (SDMT) [20], Stroop test [21] with evaluation of the total correct answers and the Pittsburgh sleep quality index (PSQI) [22].…”
Section: Evaluation Of Clinical Effectsmentioning
confidence: 99%
“…Levels of circulating soluble HTT were analyzed using a MesoScale ELISA method derived from the original ELISA assay with minor modifications [23]. The six time point samples available for 54 patients enrolled in the study were assayed for soluble HTT evaluation.…”
Section: Pharmacodynamic Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported detection of variations of HTT levels in blood samples using an ELISA method. In addition, the ELISA method could differentiate between peripheral cells isolated from healthy volunteers and HD patients at different disease stages [ 11 ].…”
Section: Methods For Identification and Quantitation Of Htt Proteimentioning
confidence: 99%